2016
DOI: 10.1590/1678-775720150240
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cervical mobilization and exercise on pain, movement and function in subjects with temporomandibular disorders: a single group pre-post test

Abstract: Objective To investigate the effect of a rehabilitation program based on cervical mobilization and exercise on clinical signs and mandibular function in subjects with temporomandibular disorder (TMD). Material and Methods: Single-group pre-post test, with baseline comparison.Subjects Twelve women (22.08±2.23 years) with myofascial pain and mixed TMD according to the Research Diagnostic Criteria for Temporomandibular Disorders.Outcome measures Subjects were evaluated three times: twice before (baseline phase) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 28 publications
0
39
0
2
Order By: Relevance
“…This promising evidence could be related to the fact that several studies have specifically reported that subjects with TMD present abnormalities of the endurance and performance of the neck flexors and extensors muscles . In particular, stabilisation exercises for the neck in combination with manual therapy for the upper cervical spine have been found to increase maximum mouth opening and to raise pressure pain threshold (PPT) in the masticatory muscles in subjects with TMD. Nevertheless, because of their methodological limitations (including lack of a control or a placebo group), these studies provided limited evidence.…”
Section: Introductionmentioning
confidence: 99%
“…This promising evidence could be related to the fact that several studies have specifically reported that subjects with TMD present abnormalities of the endurance and performance of the neck flexors and extensors muscles . In particular, stabilisation exercises for the neck in combination with manual therapy for the upper cervical spine have been found to increase maximum mouth opening and to raise pressure pain threshold (PPT) in the masticatory muscles in subjects with TMD. Nevertheless, because of their methodological limitations (including lack of a control or a placebo group), these studies provided limited evidence.…”
Section: Introductionmentioning
confidence: 99%
“…38 Another study consisted of 10 sessions of muscle-conditioning techniques, manual therapy and stretching over 5 weeks in 12 women with mixed TMD (combining myofascial pain either with joint impairment or disc displacement). 16 The results showed significant mandibular function improvement and decreased self-reported pain score. Although systematic reviews and meta-analysis observed two major issues on the majority of studies involving exercises, they did not report interventions sufficiently to be reproducible, and co-interventions were also not controlled.…”
Section: Discussionmentioning
confidence: 90%
“…All subjects reported a reduction in jaw pain after the exercise programme, classified through a numerical rating scale . Another study consisted of 10 sessions of muscle‐conditioning techniques, manual therapy and stretching over 5 weeks in 12 women with mixed TMD (combining myofascial pain either with joint impairment or disc displacement) . The results showed significant mandibular function improvement and decreased self‐reported pain score.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations